Exploring Marketing Mix Strategies in Educational Institutions: A Case Study of Madrasah Ibtidaiyah PUI Kaum Banjarsari Indonesia - Syahrul Fauzi; Santosa, Edy Yusuf Nur Samsu; Fajrin, Nidaul (Islamic Education Management Study Program, Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2023)
Purpose – This study aims to investigate the marketing mix employed by MI PUI Kaum Banjarsari in the context of educational institutions' marketing activities. Specifically, it examines the application of the standardization of New Student Admissions (PPDB) outlined in the Director General of Islamic Education's Decision Number 7265 of 2019. In a landscape with numerous educational institutions and various strategic models for attracting attention, this research seeks to understand the specific marketing mix utilized by MI PUI Kaum Banjarsari. Design/methods/approach – Conducted as qualitative-descriptive research, this study employs a field research approach involving observation, interviews with key informants possessing 3M criteria (knowing, understanding, experiencing), and documentation. The validity of the data is ensured through triangulation of sources and techniques, with interactive analysis used to interpret the findings. Findings – The research reveals that MI PUI Banjarsari Ciamis employs the marketing mix to conduct marketing activities, presenting their institution through the elements of (1) products, (2) price, (3) human resources, (4) location, (5) facilities and infrastructure; (6) process; (7) promotion. Additionally, during PPDB activities, MI PUI Kaum applies five standards to prospective students: (1) objectivity, (2) transparency, (3) accountability, (4) non-discriminatory, and (5) competitive. Research implications/limitations – The impact of this research extends to educational institutions seeking effective marketing strategies. Rules include the specific context of MI PUI Kaum Banjarsari, impacting the generalizability of the findings. Practical implications – The findings offer valuable insights for educational institutions aiming to refine their marketing strategies, particularly during the PPDB process. Understanding and implementing the marketing mix elements can enhance the institution's appeal to the public. Originality/value – This research contributes to the literature by offering a detailed examination of the marketing mix employed by MI PUI Kaum Banjarsari in the competitive landscape of educational institutions. The study's originality lies in its specific focus on the marketing dynamics during PPDB, providing valuable insights for institutions navigating similar challenges.